Chapter Impacted fluvial and coastal sediment connectivity in the Mediterranean: a brief review and implications in the context of global environmental change - Anthony, Edward (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Sediment deficits on Mediterranean coasts have resulted from anthropogenic fragmentation of rivers and loss of sediment flux connectivity caused by dams, river engineering, and aggregate extraction. Coastal sediment transport cells are now characterized by artificial boundaries that impair alongshore sediment connectivity. Climate change and sea-level rise will cause further vulnerability of the Mediterranean's fragmented rivers and coasts and there is, therefore, an urgent need to foster efforts aimed at re-establishing fluvial and alongshore sediment connectivity